COUNSELLING FOR SUSTAINABLE ECONOMIC DEVELOPMENT: PERSPECTIVES OF YOUTHS IN SAMARU-ZARIA, KADUNA STATE, NIGERIA - ABRAHAM, Jonathan, A.; OMOLADE, Oyebanji, O. O.; ADAMA, Aleke; JOY, John (Journal of Professional Counselling, 2025)
The study focuses on Counselling for Sustainable Economic Development: Perspective of Youths in Samaru-Zaria, Kaduna State, Nigeria. It was guided by two research objectives, two research questions and two hypotheses. The study adopted correlational research design. The population of the study comprises of 60 youth with small businesses in Samaru-Zaria. The researchers adopted purposive sampling techniques to select 30 participants for the study. Counselling for Sustainable Economic Development Questionnaire (CSEDQ) developed by the researchers and validated by experts in the Faculty of Education, Ahmadu Bello University, Zaria. The Null hypotheses were tested at 0.05 levels of significant using Pearson Product Moment Correlation (PPMC) statistics. It was found that there is a significant relationship between challenges of youths and sustainable economic development with (r-cal=0.615, p=0.01) and also significant relationship exists between counselling interventions and challenges of youths economic development (r=0.635,p=0.011). Basis of the findings, it was concluded that the main challenges of youths’ sustainable economic development is unemployment and corruption of embezzlement among self-fish individuals in the country. Also, Journal of Professional Counselling, Vol. 8, No. 2 81 counselling interventions play vital roles in empowering the youths through strategies and skills to drive the economic development.